2009
DOI: 10.1007/s12197-009-9105-3
|View full text |Cite
|
Sign up to set email alerts
|

Some causes of interstate differences in community bank performance

Abstract: Community Banks, Bank Performance, Regional Bank Performance, G21,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The authors found that there were significant differences between and among metropolitan area locations, however, profitability and growth of the city were positively related while profitability and population of the city were negatively related. DePrince et al (2011), looked at the effect of state demographics on the performance of community banks, between 1994 and 2008. They looked at a variety of variables including population growth, per capita income growth and the ratio of single family housing starts to the population, among others.…”
Section: Demographics and Firm Performancementioning
confidence: 99%
“…The authors found that there were significant differences between and among metropolitan area locations, however, profitability and growth of the city were positively related while profitability and population of the city were negatively related. DePrince et al (2011), looked at the effect of state demographics on the performance of community banks, between 1994 and 2008. They looked at a variety of variables including population growth, per capita income growth and the ratio of single family housing starts to the population, among others.…”
Section: Demographics and Firm Performancementioning
confidence: 99%